Podstawowe typy mezoekonomicznej polityki gospodarczej - Gorynia, Marian (Wydział Prawa i Administracji UAM, 1996)
The author discusses the levels of economic hierarchy systems, the problems of competition, the theory of branch structure and the strategy of its development. So far, the private sector has not socially functioned as well as it should. This is the basis for the state starting various activities, such as the control of profit margin, classified outlay costs, increase of prices and changes in the structures of branches.
Basic types of mezoeconomic economic policy